Optically reconfigurable shape memory metallo-polymer mediated by a carbolong complex and radically exchangeable covalent bond. Issue 13 (10th March 2022) - Yang, Liulin; Zhao, Haibo; Xie, Yulin; Ouyang, Pufan; Ruan, Yonghong; Chen, Jiangxi; Weng, Wengui; He, Xumin; Xia, Haiping
Abstract : A novel polymer network with NIR induced shape memory behaviour and plasticity. Abstract : Conventional shape memory polymers (SMPs) are restricted to predetermined permanent shapes and therefore cannot be reconfigured arbitrarily to adapt to variant application scenarios. Meanwhile, shape memory behaviour is mostly thermally active and is often induced by direct heating and lacks spatial or remote control. Herein, we report a novel SMP with a reconfigurable network containing a semi-crystalline polymer chain, radically exchangeable covalent bond and photothermoresponsive carbolong complex moiety. The photothermal effect of the carbolong complex and the thermal responsiveness of the semi-crystalline polymer chain and radically exchangeable covalent bond lead to shape memory behaviour and network topological rearrangement using near-infrared light irradiation. Such a strategy offers an opportunity for building reconfigurable shape memory polymers that can be manipulated by either direct heating or remote light irradiation.